2019
DOI: 10.1051/0004-6361/201935431
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear molecular outflow in the Seyfert galaxy NGC 3227

Abstract: ALMA observations have revealed nuclear dusty molecular disks/tori with characteristic sizes 15-40 pc in the few Seyferts and low luminosity AGN studied so far. These structures are generally decoupled both morphologically and kinematically from the host galaxy disk. We present ALMA observations of the CO(2-1) and CO(3-2) molecular gas transitions and associated (sub)-millimeter continua of the nearby Seyfert 1.5 galaxy NGC 3227 with angular resolutions 0.085 − 0.21 (7-15 pc). On large scales the cold molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 91 publications
17
45
0
Order By: Relevance
“…Six galaxies have only one peak in the field of view, and the peak coordinates agree well with the radio peaks listed in the literature as follows: IC 4518W in Condon et al (1996), NGC 1386 and NGC 7172 in Thean et al (2000), and NGC 7213 in Bransford et al (1998). NGC 3227 and NGC 5643 are discussed in detail in Alonso-Herrero et al (2019) and Alonso-Herrero et al (2018), respectively. The remaining seven show several peaks in the ALMA 1.3 mm continuum maps and are discussed below.…”
Section: Appendix A: Alma 13 MM Continuum Of Individual Sourcessupporting
confidence: 84%
See 1 more Smart Citation
“…Six galaxies have only one peak in the field of view, and the peak coordinates agree well with the radio peaks listed in the literature as follows: IC 4518W in Condon et al (1996), NGC 1386 and NGC 7172 in Thean et al (2000), and NGC 7213 in Bransford et al (1998). NGC 3227 and NGC 5643 are discussed in detail in Alonso-Herrero et al (2019) and Alonso-Herrero et al (2018), respectively. The remaining seven show several peaks in the ALMA 1.3 mm continuum maps and are discussed below.…”
Section: Appendix A: Alma 13 MM Continuum Of Individual Sourcessupporting
confidence: 84%
“…A number of works have shown that the continuum emission at 1.3 mm in Seyfert galaxies is mostly produced by synchrotron emission with varying contributions from cold dust emission and free-free emission (Pasetto et al 2019;Alonso-Herrero et al 2019;García-Burillo et al 2019). We therefore assumed that the peak of the 1.3 mm can be used to locate the position of the AGN (see also Appendix A).…”
Section: Identification Of the Agn Positionmentioning
confidence: 99%
“…We can qualitatively compare our p-v maps with those of NGC 1068 (García-Burillo et al 2019;Impellizzeri et al 2019), NGC 3227 (Alonso-Herrero et al 2019), and Circinus (Izumi et al 2018). Our model parameters are closest to those of Circinus (although at a lower γ edd ), and a similar basic structure is seen -a central 'blob', and a sharp peak of red and blue shift in the center.…”
Section: Comparison With Resolved Velocity Mapssupporting
confidence: 52%
“…High resolution ALMA observations show the molecular components of AGNs have signs of inflows, outflows, rotation, a possibly lopsided or misaligned morphology, and non-circular motions or perhaps even counterrotation (García-Burillo et al 2016;Alonso-Herrero et al 2018;Izumi et al 2018;Alonso-Herrero et al 2019;Impellizzeri et al 2019;García-Burillo et al 2019;Tang et al 2019). Infrared interferometry additionally reveals an extended polar structure, suggesting a biconical dusty wind emitted from the 'torus' region (Hönig et al 2012(Hönig et al , 2013Tristram et al 2014;López-Gonzaga et al 2016;Leftley et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al 2010;Veilleux et al 2013;González-Alfonso et al 2014 and spatially resolved with Atacama Large Millimeter Array (ALMA) observations of CO lines (e.g. Combes et al 2013;García-Burillo et al 2014;Morganti et al 2015;Pereira-Santaella et al 2018;Ramakrishnan et al 2019;Alonso-Herrero et al 2019;Husemann et al 2019). These studies reveal outflows with velocities ranging from few tens of km s −1 to over 1 000 km s −1 , mass-outflow rates of up to 10 3 M yr −1 and kinetic power as high as 10 44 erg s −1 .…”
Section: Introductionmentioning
confidence: 99%